2005
DOI: 10.1038/sj.jhh.1001843
|View full text |Cite
|
Sign up to set email alerts
|

High-dose monotherapy vs low-dose combination therapy of calcium channel blockers and angiotensin receptor blockers in mild to moderate hypertension

Abstract: The objectives of the study were to compare long-acting dihydropyridine calcium channel blockers (CCBs) with angiotensin II receptor blockers (ARBs) according to the ambulatory blood pressure monitoring (ABPM) profile in stage 1 and 2 newly diagnosed hypertensives and also to evaluate the efficacy of high-dose monotherapy vs low-dose combination therapy of the two drug categories among the subjects with inadequate blood pressure (BP) control after conventional low-dose monotherapy. We obtained 24-h ABPM readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 16 publications
2
27
1
Order By: Relevance
“…Our separate results for compliance (21% improvement: Pϭ0.02) and persistence (54% improvement: Pϭ0.07) with FDCs of antihypertensive medications are in keeping with the findings of other lessspecific reviews. 14,28 The 20% reduction in adverse events associated with the use of an FDC reported in our review is perhaps surprising but is consistent with studies published previously 33,34 and a meta-analysis 11 of 82 studies comparing FDCs of 2 antihypertensive agents with various first-line antihypertensive agents as monotherapy. This earlier meta-analysis 11 showed that the use of FDCs had a comparable or even better safety profile than single agents.…”
Section: Discussionsupporting
confidence: 75%
“…Our separate results for compliance (21% improvement: Pϭ0.02) and persistence (54% improvement: Pϭ0.07) with FDCs of antihypertensive medications are in keeping with the findings of other lessspecific reviews. 14,28 The 20% reduction in adverse events associated with the use of an FDC reported in our review is perhaps surprising but is consistent with studies published previously 33,34 and a meta-analysis 11 of 82 studies comparing FDCs of 2 antihypertensive agents with various first-line antihypertensive agents as monotherapy. This earlier meta-analysis 11 showed that the use of FDCs had a comparable or even better safety profile than single agents.…”
Section: Discussionsupporting
confidence: 75%
“…12 Combining agents that target compensatory pathways lowers BP more effectively than monotherapy. [13][14][15][16][17] Rationally selected combination therapy has the potential to mitigate adverse events, such as edema or hypokalemia, that are commonly encountered with monotherapeutic approaches. 14,18,19 The rationale for combining a CCB with a renin-angiotensin-aldosterone system (RAAS) blocker, such as an ACE inhibitor or ARB, is based on their respective mechanisms of action and subsequent vascular effects.…”
mentioning
confidence: 99%
“…There are published data suggesting that the combination of a calcium channel blocker (CCB) with an angiotensin II receptor blocker (ARB) is beneficial. 5,[7][8][9][10][11][12][13][14][15][16][17] Furthermore, such a combination approach involving adding a blocker of the renin-angiotensin system (RAS) to a CCB appears to be associated with a reduction in the incidence of CCB-related edema;…”
Section: 2mentioning
confidence: 99%
“…There are published data suggesting that the combination of a calcium channel blocker (CCB) with an angiotensin II receptor blocker (ARB) is beneficial. 5,[7][8][9][10][11][12][13][14][15][16][17] Furthermore, such a combination approach involving adding a blocker of the renin-angiotensin system (RAS) to a CCB appears to be associated with a reduction in the incidence of CCB-related edema;18 the exact mechanism for this attenuation of edema remains to be established but appears to involve the ability of RAS blockers to counteract the microcirculatory changes induced by CCBs and dilate venous capacitance vessels. 19,20 The aim of the current study was to evaluate the efficacy and safety of two different strengths of singlepill combinations (SPCs) of telmisartan 40 or 80 mg (T40 or T80) and amlodipine 5 mg (A5) compared with that of monotherapy with A5 and amlodipine 10 mg (A10) in a hypertensive patient population whose BP is not controlled by A5 alone.…”
mentioning
confidence: 99%